2001
DOI: 10.1055/s-2001-15484
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Descent: When to Interfere?

Abstract: Spontaneous descent of testes after birth can occur in up to 70% of cases, yet the factors contributing to it are still controversial. This study aims to evaluate factors contributing to spontaneous descent of palpable undescended testes. Eighty-four newborns with 126 palpable undescended testes (42 unilateral and 42 bilateral) were followed up for a period of one year to study the occurrence and time of testicular descent and its relation to gestational age, birth weight, uni- or bilaterality and levels of FS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
1
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 5 publications
4
26
1
5
Order By: Relevance
“…Their conclusion was that the optimal time to perform orchidopexy was between 6 and 12 months of age, as this was considered to maximize fertility potential and minimize malignancy risk, whilst also allowing for the spontaneous descent of the cryptorchid testis, which is reported to occur most commonly before the age of 6 months46. Their review was, however, broad in its scope, looking at general trends in the impact of age on outcome, as opposed to exploring the impact of performing orchidopexy before a specific age cut‐off.…”
Section: Discussionmentioning
confidence: 99%
“…Their conclusion was that the optimal time to perform orchidopexy was between 6 and 12 months of age, as this was considered to maximize fertility potential and minimize malignancy risk, whilst also allowing for the spontaneous descent of the cryptorchid testis, which is reported to occur most commonly before the age of 6 months46. Their review was, however, broad in its scope, looking at general trends in the impact of age on outcome, as opposed to exploring the impact of performing orchidopexy before a specific age cut‐off.…”
Section: Discussionmentioning
confidence: 99%
“…In this study only two patients; one of each group had their testis located in the abdomen, therefore the study is comparable also with regard to testicular position found at surgery. In male gonadotropin secretion which increases from 2 to 4 months after birth stimulating Leydig cells to secrete testosterone (12)(13)(14). Testosterone increase is blunted in cryptorchid boys (13,14).…”
Section: Commentsmentioning
confidence: 99%
“…In male gonadotropin secretion which increases from 2 to 4 months after birth stimulating Leydig cells to secrete testosterone (12)(13)(14). Testosterone increase is blunted in cryptorchid boys (13,14). This insufficient testosterone secretion is responsible for impaired transformation of gonocytes into Ad spermatogonia (4,5,11,(15)(16)(17).…”
Section: Commentsmentioning
confidence: 99%
“…They found that a 77.7% has a tendency of spontaneous descent at puberty, and in nearly all cases, after spontaneous descent or after pubertal orchidopexy, with long-term testicular volumes appropriate for age. Pubertal surges in luteinizing hormone and testosterone, as also is seen in the first 3 months after birth (Hamza AF et al 2001) when spontaneous descent of congenital UDT can still occur, are hypothesized to be responsible for pubertal spontaneous descent (Sijsterman K et al 2006).…”
Section: Natural Historymentioning
confidence: 99%